Perbaikan Respons Seluler pada Penuaan Hipokampus yang Diperantarai Glutation Hasil Pemberian Alanin-glutamin Dipeptida (IMPROVEMENTS CELLULAR RESPONS IN AGED HIPPOCAMPUS RELATED GLUTATHIONE RESULT OF THE ADMINISTRATION OF ALANINE-GLUTAMINE DIPEPTIDE) - ., Sunarno; Manalu, Wasmen; Kusumorini, Nastiti; Agungpriyono, Dewi Ratih (Jurnal Veteriner; Vol 14 No 1 (2013), 2013)
Physiological aging or aging due to oxidative stress decrease glutathione level in the hippocampuswhich impacts the respons impaired hippocampus celuller. Hippocampus cellular respons disorderscharacterized with decreased viability, increased mortality, and the shortening of the axons of neurons.One way to improve hippocampus cellular respons is to  increase the levels of glutathione and theconcentration of glutathione precursor. One compound that provides glutathione precursors is alanine-glutamine dipeptide. This research was designed to obtain the improve of hippocampus cellular responsresult from the administration of 7% alanine-glutamine dipeptide concentration of aged or oxidative-stressed rats. The improvement of hippocampus cellular respons affect  the improvement of the hippocampus function. The experimental rats were assigned into a completely randomized design consisted of threefactors with 2x2x2 factorial arrangement. The first factor was the age of the experimental rats, consistedof two levels i.e., 12 and 24 months. The second factor was oxidative stress consisted of two levels, i.e.,without and with oxidative stress. The third factor was alanine-glutamine dipeptide administrationconsisted of 2 concentrations, i.e. 0% and 7%. The results showed that  administration of 7% alanine-glutamine dipeptide improved level of glutathione in the hippocampus either in younger (58,76%) or aged(125,81%) rats or in normal (76,47%) and in oxidative-stressed rats (97,26%). These antioxidant hadmediated the respons improve viability, mortality, and long axons responses of neurons at younger (4,11%,37,07%, and 12,58%) or aged (6,91%, 37,85%, and 32,84%) rats, in normal (3,25%, 29,21%, and 21,04%)and oxidative stress (7,80%, 43,01%, dan 25,56%) rats. This research concluded that the alanine-glutaminedipeptide 7% increased glutathione levels.  This increased level affected the improvement of cellularresponds in aging hippocampus, physiological aging, or aging due to oxidative stress in rats.
Keywords: alanine-glutamine dipeptide, viability neuron, mortality neuron, neuron axon, glutathione, physiological aging, stress oxidative aging, hippocampus functions